Persepsi Petani Terhadap Peran Penyuluh Pertanian di Kecamatan Belopa Utara, Kabupaten Luwu, Sulawesi Selatan - Sadik, Ilham; Syafruddin, Syafruddin (Sekolah Tinggi Pertanian Kutai Timur, 2023)
The agricultural sector is the only sector that can meet food needs, which are the basic elements for meeting daily needs. One of the strategic foods for the people of Indonesia in meeting their carbohydrate needs is rice. Farming becomes more productive, effective and efficient when agricultural extension workers are involved. Extension officers provide direct guidance and act as determinants of changes in farmer behavior in developing their farming business. This research was conducted in North Belopa District, Luwu Regency. The purpose of this study was to analyze farmers' perceptions of the role of extension workers and to analyze the influence of farmer characteristics and extension activities on farmers' perceptions of the role of extension workers in North Belopa District, Luwu Regency. Determination of respondents using the slovin formula with a total of 114 respondents. The data analysis method used is the SEM (Structural Equation Modeling) analysis method which is used for the causality relationship between the variables studied. The results showed that the average score of farmers' perceptions of the role of extension workers was 7.43 on a rating scale of 1 to 10. Farmer characteristics had no significant effect on perceptions while extension activities had a significant effect on the role of extension agents in agricultural extension in North Belopa District, Kab. Luwu. Thus, extension agents need to increase their role in providing counseling to farmers so that farmers get benefits from extension activities carried out by agricultural extension workers in North Belopa District.